Sistem Pengujian Tegangan Boost Converter Pada Pembangkit ListrikTenaga Air (PLTH) Picohydro Kapasitas Rendah - M Suyanto; Subandi Subandi; Syafriyudin Syafriyudin; Isa Mubarok (Universitas Batanghari Jambi, 2020)
Voltage testing, on hybrid power plants (PLTH), uses two sources that are solar/solar power plants and waterwheel power plants. Supporting components to produce electric energy conversion one of them is boostconverter which is the main subject. Therefore the author is interested in making and testing the voltage, on the boost converter with the aim to maximize the performance of the DC Genertator as a pensupplay Batterai/accu on PLTH Pico Hydro. The DC-voltage source of the DC-DC converter can be obtained from a generator, or an AC voltage source that is air-conditioned to DC. While Dc-DC converter is a power electronic circuit, to convert a DC to DC voltage input into the output voltage with a greater value. The test results of the voltage from the field data can be concluded as follows. The voltage boost converter test results, on the Pico Hydro Hybrid power plant can produce a voltage of 13 volts from the output DC Generator 8.39 Volt. The output voltage generated by the boost converter is 13.4 volts, can be stable although the output voltage of the generator is variable. With the addition of the tool boost converter on PLTH Pico Hydro, can help battery charging/ACCU to charge the required voltage of the battery is 12 volts, from the boos convevter 13.4 volt long time charging ACCU 5.3 hours.